Pegaspargase-related high-grade hepatotoxicity in a pediatric-inspired adult acute lymphoblastic leukemia regimen does not predict recurrent hepatotoxicity with subsequent doses. (March 2018) - Burke, Patrick W.; Aldoss, Ibrahim; Lunning, Matthew A.; Devlin, Sean M.; Tallman, Martin S.; Pullarkat, Vinod; Mohrbacher, Ann M.; Douer, Dan
Highlights: Adult pegaspargase-related high-grade hepatotoxicity is common and concerning. This hepatotoxicity was often lengthy and commonly delayed subsequent cycles. Pegaspargase-related high-grade hepatotoxicity was not necessarily recurrent. Hepatotoxicity was reversible and subsequent pegaspargase delivery was not impaired. This supports pegaspargase rechallenge despite previous high-grade hepatotoxicity. Abstract: Pediatric acute lymphoblastic leukemia (ALL) regimens, including higher cumulative asparaginase doses, have been investigated in adult ALL to improve outcomes. Preliminary results are promising, but hepatotoxicity rates with long-acting pegaspargase are greater in adults than children. However, adult pegaspargase-related hepatotoxicity is not as clearly defined despite being the commonest adult toxicity. We studied the frequency and characteristics of high-grade pegaspargase-related hepatotoxicity in newly diagnosed adults on a pediatric-inspired regimen that included six planned pegaspargase doses, 2000 IU/m 2 /dose intravenously, with doses given at least four weeks apart and not discontinued or dose-reduced for previous hepatotoxicity. Pegaspargase-related toxicity was monitored weekly after 185 delivered doses and reported by NCI CTCAE v3.0. Fifty-one patients, aged 18–57, received 192 pegaspargase doses (3.8 doses/patient). High-grade hyperbilirubinemia occurred in 16 (31.4%) patients and 23 (12.4%) doses; high-grade transaminitis occurred in 33 (64.7%) patients and 62 (33.5%) doses. Of 11 patients with high-grade hyperbilirubinemia who received at least one subsequent pegaspargase dose, six (54.5%) experienced recurrent toxicity; of 24 patients with high-grade transaminitis who received at least one subsequent pegaspargase dose, 15 (62.5%) developed recurrent toxicity. Pegaspargase at this dose and interval is associated with high hepatotoxicity rates, but patients can be rechallenged despite earlier pegaspargase-related hepatotoxicity.